3D bioprinting of urethra with PCL/PLCL blend and dual autologous cells in fibrin hydrogel: An in vitro evaluation of biomimetic mechanical property and cell growth environment. (1st March 2017) - Zhang, Kaile; Fu, Qiang; Yoo, James; Chen, Xiangxian; Chandra, Prafulla; Mo, Xiumei; Song, Lujie; Atala, Anthony; Zhao, Weixin
Graphical abstract: Abstract: Objective: Urethral stricture is a common condition seen after urethral injury. The currently available treatments are inadequate and there is a scarcity of substitute materials used for treatment of urethral stricture. The traditional tissue engineering of urethra involves scaffold design, fabrication and processing of multiple cell types. Methods: In this study, we have used 3D bioprinting technology to fabricate cell-laden urethra in vitro with different polymer types and structural characteristics. We hypothesized that use of PCL and PLCL polymers with a spiral scaffold design could mimic the structure and mechanical properties of natural urethra of rabbits, and cell-laden fibrin hydrogel could give a better microenvironment for cell growth. With using an integrated bioprinting system, tubular scaffold was formed with the biomaterials; meanwhile, urothelial cells (UCs) and smooth muscle cells (SMCs) were delivered evenly into inner and outer layers of the scaffold separately within the cell-laden hydrogel. Results: The PCL/PLCL (50:50) spiral scaffold demonstrated mechanical properties equivalent to the native urethra in rabbit. Evaluation of the cell bioactivity in the bioprinted urethra revealed that UCs and SMCs maintained more than 80% viability even at 7 days after printing. Both cell types also showed active proliferation and maintained the specific biomarkers in the cell-laden hydrogel. Conclusion: These results provided a foundation for further studies in 3D bioprinting of urethral constructs that mimic the natural urethral tissue in mechanical properties and cell bioactivity, as well a possibility of using the bioprinted construct for in vivo study of urethral implantation in animal model. Significance of Statements: The 3D bioprinting is a new technique to replace traditional tissue engineering. The present study is the first demonstration that it is feasible to create a urethral construct. Two kinds of biomaterials were used and achieved mechanical properties equivalent to that of native rabbit urethra. Bladder epithelial cells and smooth muscle cells were loaded in hydrogel and maintained sufficient viability and proliferation in the hydrogel. The highly porous scaffold could mimic a natural urethral base-membrane, and facilitate contacts between the printed epithelial cells and smooth muscle cells on both sides of the scaffold. These results provided a strong foundation for future studies on 3D bioprinted urethra.